Possibilities of Science Education in Early Childhood Education (Research, Society and Development, 2022)
This paper covers a cutoff of a research project entitled O Show da Luna como possibilidade de Educação em Ciências na Educação Infantil [Luna’s Show as a possibility of Science Education in Early Childhood Education] developed within the Graduate Program in Science and Humanities Teaching of the Federal University of Amazonas, under the Study and Research Group in Early Childhood Education. The text aims to present the related analyzes in how Science Education is proposed in the planning of the classes of the 2nd Period (5-year-old children) of an Early Childhood Education institution of the city of Manaus, Amazonas, Brazil. Semi-structured interviews, on-site observations and document analysis and content of the data collected were used. The research is qualitative and is a case study developed in a public institution involving four educators. The results show that there is still a lack in the formation of Early Childhood Education teachers in order to understand what Science Education is and how it can favor the development of autonomy, curiosity, child criticality in the construction of scientific knowledge within the institution using significant practices.